2015
DOI: 10.1293/tox.2015-0031
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic antibodies: their mechanisms of action and the pathological findings they induce in toxicity studies

Abstract: Antibodies can swiftly provide therapeutics to target disease-related molecules discovered in genomic research. Antibody engineering techniques have been actively developed and these technological innovations have intensified the development of therapeutic antibodies. From the mid-1990’s, a series of therapeutic antibodies were launched that are now being used in clinic. The disease areas that therapeutic antibodies can target have subsequently expanded, and antibodies are currently utilized as pharmaceuticals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
84
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 42 publications
0
84
0
3
Order By: Relevance
“…shown that the structural residues in mouse variable regions are sufficient to elicit immune responses (24,25), leading to bioinformatic strategies to "humanize" mAbs (26)(27)(28)(29) so that >90% of the structure originates from human, with only the Ag-binding complementarity-determining region (CDR) remaining from mouse. This approach can be highly successful, as evidenced by the numerous humanized mAbs in routine clinical use (30), but is empirical and can result in decreased affinity and loss or change of specificity (26,31). The applicability of bioinformatic strategies developed to humanize mAbs to create humanized CARs is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…shown that the structural residues in mouse variable regions are sufficient to elicit immune responses (24,25), leading to bioinformatic strategies to "humanize" mAbs (26)(27)(28)(29) so that >90% of the structure originates from human, with only the Ag-binding complementarity-determining region (CDR) remaining from mouse. This approach can be highly successful, as evidenced by the numerous humanized mAbs in routine clinical use (30), but is empirical and can result in decreased affinity and loss or change of specificity (26,31). The applicability of bioinformatic strategies developed to humanize mAbs to create humanized CARs is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…cancer cytolysis by NK cells. Here, we report that an antibodyenzyme conjugate (AEC) can selectively edit the tumor cell glycocalyx and potentiate NK cell killing by ADCC, a therapeutically important mechanism harnessed by many antibody cancer drugs (30,31). We chemically fused a recombinant sialidase to the human epidermal growth factor receptor 2 (HER2)-targeting therapeutic monoclonal antibody trastuzumab (Tras).…”
mentioning
confidence: 99%
“…An alternative approach is to use antibodies that recognize cancer‐related antigens on tumor cell surfaces. Once an antibody (Ab) binds to the receptor, cancer cells are killed via Ab‐dependent or complement‐dependent cytotoxicity . This approach is selective but often demonstrates insufficient clinical activity.…”
Section: Antibody–drug Conjugatesmentioning
confidence: 99%